Structure elucidation and gene cluster characterization of the O-antigen of Yersinia kristensenii С-134. (15th July 2019) - Sizova, Olga V.; Shashkov, Alexander S.; Toukach, Philip V.; Knirel, Yuriy A.; Shaikhutdinova, Rima Z.; Ivanov, Sergei A.; Kislichkina, Angelina A.; Dentovskaya, Svetlana V.
Abstract: Mild acid degradation of the lipopolysaccharide of Yersinia kristensenii C-134 afforded a glycerol teichoic acid-like O-polysaccharide, which was studied by sugar analysis, O-deacetylation and dephosphorylation along with 1D and 2D NMR spectroscopy. The following structure of the O-polysaccharide was established: This structure is related to those of other Y. kristensenii O-polysaccharides studied earlier. The O-antigen gene cluster of Y. kristensenii С-134 was analyzed and found to be consistent with the O-polysaccharide structure established. Graphical abstract: Image 1 Highlights: Structure of the O-polysaccharide of Yersinia kristensenii C-134 was established. The O-polysaccharide has a glycerol teichoic acid-like structure. Dephosphorylation of the O-polysaccharide afforded a glycerol-linked hexasaccharide. The O-antigen gene cluster was found to be consistent with the O-polysaccharide structure.